Point-of-care hemostasis in children with congenital heart disease, the POCHEMO study: baseline reference values of thromboelastometry and impedance aggregometry. Issue 5 (July 2019) - Longchamp, David; Perez, Marie-Hélène; Natterer, Julia; Amiet, Vivianne; Ferry, Thomas; Boegli, Yann; Mauron, Sylvain; Dolci, Mirko; Plaza Wuthrich, Sonia; Di Bernardo, Stefano
Abstract : N/A: Viscoelastic tests and impedance aggregometry allow coagulation evaluation at the bedside, but reference values are scarce in pediatrics. The aim of this study was to establish reference values of thromboelastometry and impedance aggregometry for this population and compare it between age groups. This prospective, single-center, observational study evaluates viscoelastic tests and impedance aggregometry in children with congenital heart disease. A total of 204 children were included with a median age of 3.6 years old. We provide references values for this population with median, percentile 2.5 and percentile 97.5. Infants demonstrate for extrinsic activity a shorter coagulation time (52 [49–55] vs. 56 [51–62] s, P = 0.007) and clot formation time (90 [71–118] vs. 113 [93–146] s, P < 0.0001) so as for intrinsic activity a shorter clot formation time (53 [44–69] vs. 75 [59–92] s, P < 0.0001). The maximal clot firmness was significantly stronger in infants for extrinsic (65 [61–69] vs. 59 [54–63] mm, P < 0.0001), intrinsic (68 [64–70] vs. 61 [57–65] mm, P < 0.0001), and fibrinogen (12 [9–16] vs. 10 [8–13] mm, P = 0.02) activities. Platelet aggregation was significantly higher in infants with an amplitude at 6 min of 28 [23–34] vs. 22 [15–27] Ω, P less than 0.0001, a maximum speed of 11 [9–13] vs. 7 [5–10] Ω/min, P less than 0.0001, and an area under the curve of 120 [92–135] vs. 86 [59–112] Ω min, P less than 0.0001. We provided the first reference values for impedance aggregometry and thromboelastometry in children with congenital heart disease. We showed that these infants tend to have accelerated coagulation and stronger clot firmness compared with older children, but this finding may have only minimal relevance when treating a bleeding child. Trial registration number: ClinicalTrials.gov (clinicaltrials.gov/ct2/show/NCT02387944).